Mapping fire extent and burn severity in Alaskan tussock tundra: An analysis of the spectral response of tundra vegetation to wildland fire - Loboda, Tatiana V.; French, Nancy H. F.; Hight-Harf, C.; Jenkins, Liza K.; Miller, Mary Ellen (Remote Sensing of Environment, 2013)
Observed warming in the high northern latitudes has led to an increase in fire occurrence across North American tundra. Our ability to effectively monitor ecosystem change and the carbon cycle in this region depends upon the development of robust and reliable methods of extracting information about fire events and the characterization of fire impacts from remotely-sensed data. Previously developed and routinely applied remote sensing methods yield poor results in assessing the extent and severity of burning in tundra. Here we present an analysis of temporal trends in spectral signatures of burned and unburned areas of tussock tundra obtained from Landsat imagery within six fire events of the 2010 fire season in the Noatak Nature Preserve in Alaska. The analysis revealed a large variability in surface reflectance of burned and unburned areas across space and time. We established that spectral signatures of fire scars can be well separated by both single- and multi-date mapping approaches immediately after burning. However, the spectral signature of burned areas in tundra deteriorates rapidly and, in our study, is poorly distinguishable by the end of the first post-fire season. Our results showed that common mapping methods based on the normalized burn ratio were inferior to other spectral indices (Tasseled Cap Greenness and Brightness) and single Landsat bands (near-infrared) in separating burned and unburned areas as well as in mapping burn severity.